Comparing two methods of follow up in a multicentre randomised trial. Issue 4 (1st April 1997) - Fooks, Jean; Mutch, Lesley; Yudkin, Patricia; Johnson, Ann; Elbourne, Diana
Abstract : AIMS: To evaluate a parental questionnaire as a means of providing outcome measures for a multicentre randomised controlled trial of treatment for post-haemorrhagic ventricular dilatation. METHODS: The parents of 88 survivors were sent a questionnaire before a paediatric assessment at the age of 30 months. The parents' responses to individual questions taken mainly from the Griffiths' mental development scales and their perception of the child's ability to see and hear were compared with the paediatric findings. A model, based on the parents' responses to particular questions, allowed the categorisation of the children as normal, impaired, moderately or severely disabled; this was compared with similar categorisation based on the full paediatric assessment. RESULTS: Agreement on items concerning gross motor function ranged between 81 and 99%, concerning dressing between 77 and 80%, concerning feeding between 91 and 99%, and concerning language between 85 and 93%. Similar proportions of children were identified as disabled by the parents (60%) and by the paediatrician (66%). Of 29 children who had developmental quotients less than 70, parents identified 28 as disabled, 18 of them as severely disabled. They were not so good at identifying children with impairments without functional loss. CONCLUSIONS: Further work is required but there is sufficient encouragement from the results to pursue this methodology further for use in comparing groups in randomised trials.